Innovative language teaching and learning at university: enhancing participation and collaboration: an introduction - Goria, Cecila; Speicher, Oranna; Stollhans, Sascha (Research-publishing.net, 2016)
The School of Cultures, Languages and Area Studies at the University of Nottingham hosted the fifth annual conference in the "Innovative Language Teaching at University" series. Under the heading "Enhancing participation and collaboration" the conference, organised by Cecilia Goria, Oranna Speicher and Sascha Stollhans, took place on 19 June 2015, and was attended by over 120 linguists, language teachers and language acquisition researchers from all over the world. This edited volume contains 15 selected short papers based on presentations from the conference as well as Dr Jan Hardman’s keynote address and a foreword by Prof. Zoltán Dörnyei.